OHADA Uniform Accounting Act Compliance Assessment for Public Limited Companies - Michael Forzeh Fossung (Current Aspects in Business, Economics and Finance Vol. 2, 2022)
The Francophone African countries have made and continue to make remarkable efforts in harmonising the domestic financial reporting framework with the International Financial Reporting Standards (IFRS). Moving from the OCAM streams (effective 1985) to the OHADA Uniform Act (effective 2001) and now the OHADA Uniform Act on Accounting and Financial Reporting embodying 17 member countries is a milestone towards harmonisation of reporting practice domestically and internationally. This empirical study examines whether the effort of harmonisation, especially after the 2001 standards, has resulted in the successful convergence of firms’ accounting practices. Specifically, the study investigates the extent to which public limited liability companies comply with the OHADA Uniform Act and whether such compliance has improved over time. Three public limited firms in the OHADA zone that convert their financial statements into IFRS provided their annual reports for 2008 and 2009, which were used in the study. Data analysis has employed the closeness ranks and compliance index. Findings reveal a relatively high level of compliance with the OHADA Uniform Act on Accounting and Financial Reporting. The findings also show harmonisation in the accounting practices of limited companies within member countries, as they were discovered to be substantially consistent in compliance, particularly in countries that have implemented the Statistics and Tax Returns (or "DSF") as a reporting system.